PEMBUATAN DAN KARAKTERISASI ARANG AKTIF DARI BAMBU APUS (Gigantochloa apus) DENGAN AKTIVATOR H3PO4 - Manurung, M.; Sahara, E.; Sihombing, P. S. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019, 2019)
This paper discusses the manufacture and characterization of activated carbon from bamboo apus ( Gigantochloa apus ) with H 3 PO 4 activator. The aims of study were to determine the optimum carbonization temperture and  time as well as the amount of phosphoric acid required as the chemical activator. In addition, the activated carbon was also characterized following the Indonesian National Standard (SNI-1995) for activated carbon. Tthe activated carbon functional groups was determined using FTIR spectroscopy. The result showed that the optimum temperature of carbonization was 600 o C, the carbonization time was 90 minutes and the  phosphoric acid  required was 20 gram for 1 gram carbon. Under these conditions, the activated carbon resulted met SNI-1995 with the characteristics as follows:  the water content was (1.11±0.83%), the level of volatile substances was (8.13± 0.27%), the total ash amount was (7.33±1.35%), the carbon contents was (83.40±0.27%). and the absorption capacities of iodine and methylen blue were of 1057.75 mg/g, 472.88 mg/g, respectively. FTIR identification indicated the existence of some functional groups, namely aromatik, ketone, and hydroxyl.